An algorithm for solving the stationary flow equation with fine grid segments in a confined-unconfined aquifer - Gubajdullin, D.A.; Mazurov, P.A.; Tsepaev, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2005)
An algorithm for multiprocessor computing systems has been developed to solve the flow equation for a confined-unconfined aquifer on a coarse grid with fine grid segments near wells. The efficiency of this algorithm increases with increasing number of fine grid segments.